Circular RNAs: Potential Regulators of Treatment Resistance in Human Cancers - Jeyaraman, Shivapriya; Hanif, Ezanee Azlina Mohamad; Ab Mutalib, Nurul Syakima; Jamal, Rahman; Abu, Nadiah (Frontiers in Genetics, 2020)
Circular RNAs (circRNAs) which were once considered as ‘junk' are now in the spotlight as a potential player in regulating human diseases especially cancer. With the development of high throughput technologies in recent years, the full potential of circRNAs is being uncovered. CircRNAs possess some unique characteristics and advantageous properties that could benefit medical research and clinical applications. Moreover, circRNAs are stable with covalently closed loops that are resistant to ribonucleases, have disease stage-specific expressions and are selectively abundant in different types of tissues. Interestingly, the presence of circRNAs in different types of treatment resistance in human cancers was recently observed with the involvement of a few key pathways such as the Wnt, MAPK and PI3K/AKT pathways. The activation of certain pathways by circRNAs may give new insights to treatment resistance management. The potential usage of circRNAs from this aspect is very much in its infancy stage and has not been fully validated. This mini-review attempts to highlight the possible role of circRNAs as regulators of treatment resistance in human cancers based on its intersection molecules and cancer-related regulatory networks.